2016
DOI: 10.1016/j.neulet.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Highly specific changes in antioxidant levels and lipid peroxidation in Parkinson’s disease and its progression: Disease and staging biomarkers and new drug targets

Abstract: There is evidence that immune-inflammatory, stress of reactive oxygen and nitrogen species (IO&NS) processes play a role in the neurodegenerative processes observed in Parkinson's disease (PD). The aim of the present study was to investigate peripheral IO&NS biomarkers in PD. We included 56 healthy individuals and 56 PD patients divided in two groups: early PD stage and late PD stage. Plasma lipid hydroperoxides (LOOH), malondialdehyde (MDA), nitric oxide metabolites (NOx), sulfhydryl (SH) groups, catalase (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 28 publications
5
67
0
1
Order By: Relevance
“…Considering the increased %HNA in iPD compared with controls regardless of disease duration, age‐induced oxidative stress may trigger disease onset . Previously, several investigations have revealed oxidative stress‐related compounds as diagnostic biomarkers of iPD . Our study confirmed the significance of lower serum levels of UA, which is a powerful antioxidant in iPD (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Considering the increased %HNA in iPD compared with controls regardless of disease duration, age‐induced oxidative stress may trigger disease onset . Previously, several investigations have revealed oxidative stress‐related compounds as diagnostic biomarkers of iPD . Our study confirmed the significance of lower serum levels of UA, which is a powerful antioxidant in iPD (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…25 Previously, several investigations have revealed oxidative stress-related compounds as diagnostic biomarkers of iPD. 26,27 Our study confirmed the significance of lower serum levels of UA, which is a powerful antioxidant in iPD 28 (Fig. 4A).…”
Section: Discussionsupporting
confidence: 80%
“…Although our findings point out to a lack of an association between endogenous antioxidant changes in PD peripheral tissue, a recent study has described specific plasmatic changes in antioxidant levels and lipid peroxidation as potential promising PD biomarkers [36]. …”
Section: Discussionmentioning
confidence: 75%
“…Asparagine was increased in CSF and blood plasma, but it decreased in serum in PD patients. Elevated sorbitol and propylene glycol levels were also observed in PD patients (Ahmed et al, 2009;de Farias et al, 2016;González-Domínguez et al, 2014a;Gröger et al, 2014;Luan et al, 2015;Marklund and Marklund, 1974;Trupp et al, 2014;Wang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%